Fiscal Policy, Economic Adjustment, and Financial Markets. (International Monetary Fund, 1989)
Edited by Mario Monti, this volume contains the proceedings of a seminar that was held in Milan at the Centre for Financial and Monetary Economics, Universita Luigi Bocconi. Participants included government officials, academicians, and economists; they provide a many-faceted view of fiscal policy at the domestic level and in the broader context of international policy coordination.